2018
DOI: 10.25159/2415-5829/2320
|View full text |Cite
|
Sign up to set email alerts
|

African Indigenous Knowledge and Social Work Practice: Towards an Afro-sensed Perspective

Abstract: South Africa is a multicultural society with diverse indigenous cultural communities. It has been argued that as Africa enters into a new phase of knowledge development, disciplines like social work are equally asked to rethink their methods and theories to embrace this emerging challenge. The central idea of this article is based on the presumption that social workers should intervene in a culturally-sensed manner, appropriately and seeking to discover uniqueness in local indigenous ways within specific commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…In contrast, indigenous social work actively centres indigenous cultural knowledges, beliefs and ways of being and doing, highlights intergenerational impacts of colonisation and considers Western knowledge as complementary (Gray et al, 2008). Afrocentrism exemplifies an indigenous perspective (Makhubele, Matlakala & Mabvurira, 2019;Mathebane & Sekude, 2018;Shokane & Masoga, 2018). As a further alternative, decolonised social work and decoloniality foreground the ways in which Western discourses and assumptions create and reproduce historical and current subjugation (Harms-Smith & Nathane, 2018;Mathebane & Sekudu, 2018).…”
Section: Alternatives To the Dominant Approachesmentioning
confidence: 99%
“…In contrast, indigenous social work actively centres indigenous cultural knowledges, beliefs and ways of being and doing, highlights intergenerational impacts of colonisation and considers Western knowledge as complementary (Gray et al, 2008). Afrocentrism exemplifies an indigenous perspective (Makhubele, Matlakala & Mabvurira, 2019;Mathebane & Sekude, 2018;Shokane & Masoga, 2018). As a further alternative, decolonised social work and decoloniality foreground the ways in which Western discourses and assumptions create and reproduce historical and current subjugation (Harms-Smith & Nathane, 2018;Mathebane & Sekudu, 2018).…”
Section: Alternatives To the Dominant Approachesmentioning
confidence: 99%
“…Natural hazards are unavoidable; they disrupt the daily lives of people and communities, can result in substantial loss of life and cause social upheaval (Shokane 2017 ; Zakour & Gillespie 2017 ). In addition, Sarma et al ( 2020 ) concurred that disasters are unpredictable occurrences of a series of disruptions within a period, which cease the functioning of a society, with potential great loss of human lives and property, as well as impacting the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, the literature further confirmed that natural hazards occur in different parts of the world and many social work professionals are engaged in the disaster relief process, but with only a few documented in a South African context. The only observation of emerging natural hazard research in South Africa focusing on community social work and natural hazards by environmental-social work scholars such as Shokane and Nel ( 2017 ), as well as Rinkel and Powers ( 2017 ), with Masoga and Shokane ( 2019 ), Lombard and Twikirize ( 2018 ) and Shokane ( 2017 , 2017 , 2019 ), ‘have the potential to contribute to an environmentally effective social work practice’ (Marlow & Van Rooyen 2001 :252). Thus, social work disaster management and community intervention approaches should tackle the impact of disasters, and seek to make individuals, communities and societies more resilient and less vulnerable to shocks and stresses (Davies et al 2008 ; Tanner & Mitchell 2008 ; Zakour & Gillespie 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By official knowledge we mean universal North-centric knowledge that is commonly taught in universities and public schools, as opposed to contextual indigenous and informal knowledges (e.g. Jain, 2013;Shokane and Masoga, 2018). Therefore, it is important to ask what knowledge is used and how knowledge can enable or prevent us from recognizing, examining and challenging power relations.…”
Section: Introductionmentioning
confidence: 99%